2007
DOI: 10.1103/physrevd.75.084013
|View full text |Cite
|
Sign up to set email alerts
|

Spacetimes with longitudinal and angular magnetic fields in third order Lovelock gravity

Abstract: We obtain two new classes of magnetic brane solutions in third order Lovelock gravity. The first class of solutions yields an (n + 1)-dimensional spacetime with a longitudinal magnetic field generated by a static source. We generalize this class of solutions to the case of spinning magnetic branes with one or more rotation parameters. These solutions have no curvature singularity and no horizons, but have a conic geometry. For the spinning brane, when one or more rotation parameters are nonzero, the brane has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Solutions with longitudinal and angular magnetic field were considered in Refs. [9][10][11][12]. Similar static solutions in the context of cosmic string theory were found in Ref.…”
Section: Introductionsupporting
confidence: 84%
“…Solutions with longitudinal and angular magnetic field were considered in Refs. [9][10][11][12]. Similar static solutions in the context of cosmic string theory were found in Ref.…”
Section: Introductionsupporting
confidence: 84%
“…Solutions for more complicated variants of the theory are not large in number. Investigations of third order Lovelock gravity (without dilaton) can be found in [10,11,12], studies of the second order with dilaton can be found in [13,14]. Moreover, C. C. Briggs obtains explicit formulae for the 4-th and 5-th Lovelock tensors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, up to now only the lowest order Lovelock correction, i.e. the Gauss-Bonnet term, has been extensively studied [16,17], with recent attempts to also include a third and fourth order density [18,19,20,21].In this letter we discuss an alternative method of calculating the first Lovelock densities, based on the use of permutation diagrams, instead of the more conventional way of using the Kronecker permutation tensor. We demonstrate that this method can lead to dramatic simplification of certain calculations, rendering the derivation of the first few scalar densities almost trivial.…”
mentioning
confidence: 99%
“…As a result, up to now only the lowest order Lovelock correction, i.e. the Gauss-Bonnet term, has been extensively studied [16,17], with recent attempts to also include a third and fourth order density [18,19,20,21].…”
mentioning
confidence: 99%